Analysis of Bread Production Quality at SMEs Industry using Statistical Process Control (SPC) - Tessa Zulenia Fitri; Rama Dani Eka Putra; Foci, Nia Arfina; Yasin, Muhamad; Munanda, Muhammad Arif (Journal of Engineering Science and Technology Management, 2025)
XYZ Industry is a micro-enterprise engaged in bread production. However, defects such as burnt bread, irregular shapes, and inconsistent weights are still frequently found during production, which affects customer satisfaction and production efficiency. This study aims to analyze and optimize bread production quality using the Statistical Process Control (SPC) approach. The methodology includes data collection over 20 production days, analysis using Pareto diagrams, p control charts, and R charts, and cause and effect diagrams. The findings indicate an average defect rate of 4.79%, with burnt bread being the most prevalent defect (30%). The p control chart identified several days with assignable variation, while the and R charts revealed that the bread weight process was statistically in control. The main causes of defects were related to human factors, machine limitations, and the absence of standardized procedures. Recommendations include establishing standard operating procedures (SOPs), conducting operator training, and procuring supporting tools. The consistent application of SPC is expected to enhance both the quality and efficiency of production